Congenital syphilis neonatal alterations in a university hospital in Niterói - RJ - Souza, Philippe Godefroy C de (2013)
Introduction: Syphilis is a sexually transmitted disease caused due to bacterium Treponema pallidum. The prevalence of this infection decreased significantly by the use of penicillin, but it is observed that it reappears particularly in cases of congenital syphilis (CS). Objective: to describe the effects of neonatal CS in newborns (NB) in a public hospital in Niterói - RJ, from January 2005 to June 2006 and to observe the birth weight and serology of newborns with CS notification. The purpose of this study is also to describe the CS treatment in each case. Methods: a sample of 35 CS notifications was recorded from the Center for Hospital Surveillance at the Antonio Pedro University Hospital (HUAP), Niterói - RJ, from January 2005 to June 2006. Data from the notifications was used and home visit was done to collect blood samples. Results: the study population is comprised of 29 live birth patients, four miscarriages and two stillbirths. Only two cases (6.9%) had evidence of CS bone abnormalities. The VDRL test performed in cerebrospinal fluid (CSF) of the cases proved to be non-reactive for all patients. VDRL serum of newborns at birth was positive for 23 (79.31 %) patients. The crystalline penicillin G was administered in 26 (89.65 % cases,) procaine penicillin G in two (6.9%) and for one individual both crystalline penicillin G and procaine penicillin G was used. Conclusion: fetal death and abortion were the most ominous outcome and impact of CS. Long bones alterations were scarcely found in few samples. Low birth weight was observed in a few cases. CSF VDRL was not reactive in all cases. The use of several antibiotic regimens was in disagreement with the proposed protocol issued by the Ministry of Health.